Organismos, movimientos, campos, espacios, escenarios. En torno a los debates sobre la definición de las luchas por los derechos humanos en Argentina - Alonso, Luciano (Historiografías, 2021)
Abstract From the period of transition to democracy in Argentina onwards, there have been different alternatives concerning the concepts to discuss in what consists of the collective actions in defense of human rights. Probably what is at stake in these debates is not only the way of naming and defining an object of study, but the very possibility of explaining with precise and exclusive words the open and indeterminate nature of certain socio-political practices. In this way, this paper reviews the theoretical assumptions in the construction of analytical categories, and concludes by advocating a certain conceptual pluralism, which facilitates the academic discourses to account for the material complexity of the past. Keywords Human Rights, analytical categories, descriptive concepts, conceptual pluralism